Neurofibromatosis - Sharma, D; Murki, S; Madhavi, V (Journal of Nepal Paediatric Society, 2014)
Neurofibromatosis is a genetically-inherited disorder in which the nerve tissue grows tumors (neurofibromas) that may be benign and may cause serious damage by compressing nerves and other tissues. Neurofibromatosis is an autosomal dominant disorder, which means only one copy of the affected gene is needed for the disorder to develop(1). We report a baby who was admitted with us in view of prematurity (34 weeks gestation ) and low birth weight (1.32 Kg). Baby’s mother was antenatally diagnosed with NF 1(figure no 1,2). Baby had multiple café au lait spots all over the bodies (figure no 3,4). Baby was discharged from nursery in well condition. DOI: http://dx.doi.org/10.3126/jnps.v34i1.8535 J Nepal Paediatr Soc 2014;34(1):81-82